Research in industry : festschrift volume in honour of Prof. K.K.G. Menon - Menon, K. K. G.; Mulky, M. J.; Srivastava, H. C.; Vatsya, Bhartendu (New Delhi : Oxford & IBH Pub. Co., 1987)
Festschrift honoring a scientist in the Hindustan Lever; comprises chiefly his unpublished papers, transcript of his unpublished lectures, and summary of his published papers.
Includes bibliographies.
Keywords: Menon, K. K. G; Research, Industrial